Design of Experimental Setup for Imitation Modeling of the Radar System for Personnel Screening in Motion - Zhuravlev, A.; Dong, G.; Razevig, V.; Chizh, M.; Hu, B. (2019 Photonics & Electromagnetics Research Symposium - Fall (PIERS - Fall), 2019)
This paper describes the setup and the experiment technique that were used to imitate the performance of the new microwave personnel screening system. Its concept is based on the use of the relative motion of the subject in the vicinity of a sparse stationary antenna array to obtain both synthetic aperture, required to attain high radar image resolution, and multi-view geometry. The ambiguity of the subject's position and pose during the radar signal processing in the system is removed by the use of an RGB-D sensor that captures the depth map of the scene. Advantages and limitation of the experimental setup and technique are presented along with selected experimental results. Further development of the setup and the experimental technique is suggested.